Dietary fat in relation to all‐cause mortality and cancer progression and death among people with metastatic colorectal cancer: Data from CALGB 80405 (Alliance)/SWOG 80405. Issue 2 (20th August 2022) - Van Blarigan, Erin L.; Ma, Chao; Ou, Fang‐Shu; Bainter, Tiffany M.; Venook, Alan P.; Ng, Kimmie; Niedzwiecki, Donna; Giovannucci, Edward; Lenz, Heinz‐Josef; Polite, Blase N.; Hochster, Howard S.; Goldberg, Richard M.; et al.
Abstract: Data on diet and survival among people with metastatic colorectal cancer are limited. We examined dietary fat in relation to all‐cause mortality and cancer progression or death among 1149 people in the Cancer and Leukemia Group B (Alliance)/Southwest Oncology Group (SWOG) 80405 trial who completed a food frequency questionnaire at initiation of treatment for advanced or metastatic colorectal cancer. We examined saturated, monounsaturated, total and specific types (n‐3, long‐chain n‐3 and n‐6) of polyunsaturated fat, animal and vegetable fats. We hypothesized higher vegetable fat intake would be associated with lower risk of all‐cause mortality and cancer progression. We used Cox proportional hazards regression to estimate adjusted hazard ratios (HR) and 95% confidence intervals (CI). Over median follow‐up of 6.1 years (interquartile range [IQR]: 5.3, 7.2 y), we observed 974 deaths and 1077 events of progression or death. Participants had a median age of 59 y; 41% were female and 86% identified as White. Moderate or higher vegetable fat was associated with lower risk of mortality and cancer progression or death (HRs comparing second, third and fourth to first quartile for all‐cause mortality: 0.74 [0.62, 0.90]; 0.75 [0.61, 0.91]; 0.79 [0.63, 1.00]; P trend: .12; for cancer progression or death: 0.74 [0.62, 0.89]; 0.78 [0.64, 0.95]; 0.71 [0.57, 0.88]; P trend: .01). No other fat type was associated with all‐cause mortality and cancer progression or death. Moderate or higher vegetable fat intake may be associated with lower risk of cancer progression or death among people with metastatic colorectal cancer. Abstract : While dietary factors are associated with survival in nonmetastatic colorectal cancer patients, data on diet and survival among individuals with advanced or metastatic disease is limited. In this analysis, dietary fat intake was investigated in relation to mortality and cancer progression or death among advanced or metastatic colorectal cancer patients. Individuals with moderate or higher vegetable fat intake, paralleled by lower animal fat intake, had a lower risk of cancer progression or death relative to patients with low vegetable fat intake. Replacing moderate amounts of animal fat with vegetable fat may be associated with longer progression‐free survival among advanced or metastatic colorectal cancer patients.